Are ballot box issues enough? Nakanishi's indication and the case for Asian Pacific American transnational politics in an age of domestic disruption. (3rd July 2018) - Collet, Christian
ABSTRACT: The occasion of honoring Don Nakanishi presents an opportunity to reflect on the challenge of understanding Asian Pacific American politics amid the dueling forces of rapid globalization and disruption to domestic institutions. Observing that the study of APAs in political science has largely developed along the lines of voting behavior, the case is made for recognizing Nakanishi's long standing call for an inclusive, internationalized field that defines participation broadly and positions it transnationally. A review of what survey research has yielded on APA transnational politics suggests significant variations among sub-groups as well as several directions for future work in this burgeoning scholarly domain.